Digital transformation of the promotion of educational services of Kazakhstani universities - Venera Zarubina; Mikhail Zarubin; Zhaukhar Yessenkulova; Rassima Salimbayeva; Gulbarshyn Satbaeva (Journal of Innovation and Entrepreneurship, 2024)
Digital channels have become the modern priority channels for promoting educational services. Integration into the international educational space, changes in the priority of communication channels, and digital transformation have led to the need to rethink existing approaches to the digital promotion of educational services of Kazakhstani universities. Particular interest in modernizing the promotion of educational services is caused by the fact that representatives of the new generation, Generation Z, are now becoming consumers of educational services. The basis of this study was the analysis of digital promotion channels as the main source of information and value, the needs of generation Z, who are now becoming the main consumers of the services of universities, including those in Kazakhstan. The purpose of the study is to determine the priorities for the digital promotion of educational services, to build a model for the digital promotion of university educational services, taking into account the needs of key consumers-generation Z, digital channels, and educational programs of the university. Hypothesis: priorities for digital promotion of educational services of universities should be differentiated depending on the popularity and technical parameters of the sites. The web resources similarweb.com, pagespeed.web.dev, wordstat.yandex.ru, sitechecker.pro were used as analysis tools. A correlation analysis of queries on university websites and the core values of generation Z was carried out. The closeness of the pairwise correlation between the total number of visits and website performance, search engine optimization, recommendations, and special features was determined. Based on the research, a model for promoting the university's educational services has been structured, highlighting key components: educational programs, digital technologies, and the values of generation Z.
Keywords: 650; Digital marketing; Generation Z; Kazakhstan; Model for promoting educational services of the university; Promotion channels; Promotion of educational services